Effect immunomodulator of CXCL10 in mice BALB/C infected with Leishmania braziliensis refractory to antimony - Brunheld Maia Dutra (2015)
Leishmania braziliensis from antimony-resistant patient is able to induce high levels of IL-4 and Arginase in mice, contributing to the increased virulence of the strain and the severity of the disease. CXCL10 is a chemokine that recruits and activates Th1 cells, NK, macrophages, dendritic cells and lymphocytes B. The objective of this study was to evaluate in vivo the effect of CXCL10 in the infection by strain of L. braziliensis refractory to treatment with antimony. BALB/c mice (n=64) were infected intradermally in the right ear 107 promastigotes (20 Âl), and after appearance of lesions (5Â week), the animals were divided into four groups (16/group): 1. Control untreated; 2.Glucantime (100mg/kg/day, I.M.); 3.CXCL10 (100 ng/10μL, I.M.); 4.Glucantime+CXCL10 (100ng/10ÂL+100mg/kg/day, I.M.). The animals were treated for 7 days, followed by weekly measurements of lesions, and were euthanized in the first and fourth week post-treatment (w.p.t) for the evaluation of some parameters: parasite burden (lesions, and draining lymph node-LN), production of the cytokines IFN-γ, IL-4, IL-10 and TGF-β (LN) and histological changes (lesions). The results showed CXCL10 and Glucantime induced, early as the first s.p.t., non-ulcerated lesions that regressed significantly (0.35 Â 0.07, 0.047 Â 0.27, p <0.05) compared to controls (0.63 Â 0.12) and Glucantime (0.56 Â 0.12). This was associated with a significant decrease in parasite load observed in CXCL10 and CXCL10 + Glucantime groups, in the lymph node (1.17x103 Â 0.85x103, 2.05x103 Â 1.50x103, respectively) compared to control (3.2x104 Â 1.97x104) and Glucantime (1.18x105 Â 1.12x105). Regarding to cytokines, CXCL10 treated animals showed high levels of IFN-γ, IL-10 and TGF-β, and low IL-4 production. In contrast, was observed in the control and Glucantime groups increased production of IL-4. These data also corroborate the histopathological findings showing that animals treated with CXCL10, with or without Glucantime, showed a non-exacerbated inflammation, with absence of necrosis, lower parasitism, granulomas and cellular infiltrate with more activated macrophages, many lymphocytes and few plasma cells, compared to control and Glucantime. In conclusion, CXCL10 and the association CXCL10+Glucantime induced minor injuries, lesions non-ulcerated, with decreased earlier parasite load, leading to the resolution of the disease through an immune response with high IFN-γ and low IL-4 production, and with the control of inflammation mediated by IL-10 and TGF-β.